Scientific Approach to Promote Scientific Writing Skills using Blended Learning System - et.al, Dewi Suprihatin, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
This study explores students’ scientific writing skills using the blended learning system. The qualitative method was used to improve students' scientific writing skills in learning the Indonesian language general course. The scientific approach is a learning process designed to observe, question, try, reason, and communicate. It encourages the development of attitudes, knowledge, and skills of students to meet scientific principles. This leads to factual, conceptual, procedural, or metacognitive knowledge, which can be obtained through sensory experiences from various sources. The current preliminary study is very good and appropriate in learning the Indonesian language general course, especially for non-Indonesian students. The presence of information technology also provides a wider learning opportunity for observation. Data were collected through qualitative observation, namely taking notes and recording humanistic counseling from interviews with Indonesian language general course lecturers. The result showed that one of the essential ways to improve students' scientific writing skills are by combining learning with a blended learning system. This can support their success in completing the final project and the workload of each course. A lecturer plays an important role in producing scholars with academic knowledge and also other skills using scientific approaches with blended learning system. Therefore, this study describes lecturers' scientific approach with a blended learning system from theory to practice.